Cutaneous Adnexal Neoplasms - Requena, Luis; Sangüeza, Omar (Springer International Publishing : Imprint: Springer, 2017)
This superbly illustrated book is the most comprehensive available guide to adnexal neoplasms of the skin. More than 70 entities are described in individual chapters that follow a uniform structure: historical review, clinical features, histopathology, histogenesis, immunohistochemistry, molecular anomalies, and treatment. Readers will find state of the art knowledge on all aspects, including the cytogenetic and chromosomal abnormalities associated with each neoplasm. Without exception, the illustrations are high-quality, full-color, original digital pictures. The histopathology images are taken from perfectly cut and stained sections and the immunohistochemistry illustrations are of an unrivalled quality among textbooks of dermatology and dermatopathology. A complete list of references from original description to the present day is also supplied for each neoplasm. Cutaneous adnexal neoplasms are a large and heterogeneous group of benign and malignant lesions. This book will assist the reader in early and correct recognition, which is essential for appropriate choice of treatment and prognostic assessment.
Keywords: Medicine.; Immunology.; Dermatology.; Oncology.; Pathology.; elektronické knihy; electronic books